2021
DOI: 10.24200/sci.2021.53630.3339
|View full text |Cite
|
Sign up to set email alerts
|

Efficient scheduling of emergency surgeries by adjusting the schedule of elective surgeries

Abstract: The rapid growth of the population has resulted in an increasing demand for healthcare services, which forces managers to use costly resources such as operating rooms effectively. The surgery-scheduling problem is a general title for problems that consists of the patient selection and sequencing of the surgeries at the operational level, setting their start times, and assigning the resources. Hospital managers usually encounter elective surgeries that can be delayed slightly and emergency surgeries whose arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Constraint (6) calculates the overtime of the OR. Constraint (7) calculates the idle time of the OR. Constraint (8) indicates the surgeon's preferences in the assigned blocks to him/her.…”
Section: The First Mip Model With a Probabilistic Los (Model I)mentioning
confidence: 99%
See 1 more Smart Citation
“…Constraint (6) calculates the overtime of the OR. Constraint (7) calculates the idle time of the OR. Constraint (8) indicates the surgeon's preferences in the assigned blocks to him/her.…”
Section: The First Mip Model With a Probabilistic Los (Model I)mentioning
confidence: 99%
“…In a weekly planning horizon, the MSS problem assigns surgeons to a particular OR time block, day, and room [6]. In operational planning, the decisions are made for daily and weekly periods [7]. The scheduling procedure for the surgical department in nearly all hospitals has two principal steps.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the Pareto frontiers in Figure (5) for these two scenarios to the original scenario, it is concluded that decreasing the difference in preference coefficients for academic degrees results in an increase in the amount of preferences satisfied.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Scheduling has been researched and studied for many years as one of the well-known combinatorial optimization problems. Numerous studies have been conducted in this field of optimization in a variety of fields, including manufacturing [1], transportation [2,3], healthcare [4,5], sports [6], and education [7]. [8].…”
Section: Introductionmentioning
confidence: 99%